Endoscopic resection for a solitary Peutz‐Jeghers type polyp in the duodenum: A case report with literature review - Yasuhiko Hamada; Masaki Katsurahara; Yuhei Umeda; Yohei Ikenoyama; Akina Shigefuku; Yasuko Fujiwara; Tuyoshi Beppu; Junya Tsuboi; Reiko Yamada; Misaki Nakamura; Kyosuke Tanaka; Noriyuki Horiki; et al. (DEN Open)
Abstract A 68‐year‐old female patient was referred to our hospital with a 30‐mm polyp in the second portion of the duodenum found via esophagogastroduodenoscopy. The polyp had an irregular, lobular surface and a thick stalk. In addition, white dots were detected on the surface. Magnifying endoscopy with narrow‐band imaging showed a white material deep in the loop‐shaped microvessels on the white dots. Endoscopic ultrasonography showed a hypoechoic elevated lesion from the mucosal layer, and a feeding vessel traversing the stalk to supply the head of the polyp. Endoscopic biopsy did not provide a definitive diagnosis. Endoscopic resection was conducted for a definitive diagnosis and treatment. The resected specimen showed a branching bundle of smooth muscle fibers covered by hyperplastic mucosa, consistent with a hamartomatous polyp. The patient had no mucocutaneous pigmentation or familial history of the hamartomatous polyp. The polyp was finally diagnosed as a solitary Peutz‐Jeghers‐type polyp. No recurrence has been observed for seven years postoperatively.